Pengaruh Konsumsi Jambu Biji terhadap Peningkatan Jumlah Trombosit Pasien Demam Berdarah Dengue - Darmaningrat, Asvini (Nutriology : Jurnal Pangan, Gizi, Kesehatan, 2023)
Dengue hemorrhagic fever or DHF is an infectious disease caused by the dengue virus and characterized by thrombocytopenia. Thrombocytopenia that persists in DHF can cause life-threatening complications. Monitoring the platelet count, in addition to the hematocrit level, is important to determine the severity of DHF. Therapy for DHF currently focuses on supportive and symptomatic therapy. Alternative therapy using guava (Psidium guajava L.) is believed to help the healing process of DHF by increasing the number of platelets. This study aims to determine the effect of consuming guava on increasing the number of platelets in DHF patients. The method used is to search literature according to the topic through the Google Scholar database with the keywords (jambu biji) OR (Psidium guajava) AND trombosit OR thrombocyte AND (demam berdarah dengue) OR (dengue hemorrhagic fever) in the period 2017-2022. Some literature states that the consumption of guava has a significant effect on increasing the number of platelets in DHF patients. Guava contains the flavonoid compounds quercetin and vitamin C which play a role in the production of platelets and inhibits the replication of the dengue virus.